2018
DOI: 10.1016/j.yhbeh.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin modulates mate-guarding behavior in marmoset monkeys

Abstract: In socially-monogamous species, intolerance of interactions between a pairmate and a sexual rival (i.e., mate-guarding) promotes the preservation of long-lasting partnerships. One promising neurobiological candidate for the regulation of mate-guarding behavior in monogamous primates is the oxytocin (OT) system, given its established role in both the development of monogamous bonds and the behavioral processes that facilitate the preservation of those bonds. In this study, male and female marmosets were exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 95 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…Studies in humans have also shown an association between increased aggression, competition, and OXT (DeWall et al, 2014; Ne’eman et al, 2016; De Dreu, 2012; Fischer-Shofty et al, 2013). However, studies in monogamous marmosets (Cavanaugh et al, 2018), monogamous titi monkeys (Witczak et al, 2018), female and male rats (De Jong et al, 2014; Calcagnoli et al, 2013; Calcagnoli et al, 2015a; Calcagnoli et al, 2015b), house mice primed for aggressive behavior due to social isolation (Tan et al, 2019), and house mice bred for callous traits (Zoratto et al, 2018) found that OXT was associated with reduced intrasexual competition and aggression. Together with our data, these findings suggest that OXT’s effect on intrasexual aggression may depend heavily on the species, brain areas activated by OXT, and social context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in humans have also shown an association between increased aggression, competition, and OXT (DeWall et al, 2014; Ne’eman et al, 2016; De Dreu, 2012; Fischer-Shofty et al, 2013). However, studies in monogamous marmosets (Cavanaugh et al, 2018), monogamous titi monkeys (Witczak et al, 2018), female and male rats (De Jong et al, 2014; Calcagnoli et al, 2013; Calcagnoli et al, 2015a; Calcagnoli et al, 2015b), house mice primed for aggressive behavior due to social isolation (Tan et al, 2019), and house mice bred for callous traits (Zoratto et al, 2018) found that OXT was associated with reduced intrasexual competition and aggression. Together with our data, these findings suggest that OXT’s effect on intrasexual aggression may depend heavily on the species, brain areas activated by OXT, and social context.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, OXT can increase envy, schadefreude, defensive but not offensive aggression toward a competing out-group, and domestic violence in men prone to aggression (Shamay-Tsoory et al 2009; Bethlehem et al, 2015; De Dreu et al, 2016; De Dreu et al, 2010; DeWall et al 2014). OXT is also associated with increased mate guarding in rats (Holley et al, 2015), prairie voles (Bales & Carter 2003), and marmoset monkeys (Cavanaugh et al, 2018). Furthermore, OXT is associated with increased maternal aggression toward potential predators (Bosch & Neumann 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports studying social behavior found that oxytocin (OT) and arginine-vasopressin (AVP) signaling directly impact behaviors associated with pair bonding, such as attachment, social recognition, aggression, parental care, and socio-sexual motivation ( Winslow et al, 1993 ; Williams et al, 1994 ; Insel and Hulihan, 1995 ; Insel, 1997 ; Young et al, 1998 ; Cho et al, 1999 ; Pitkow et al, 2001 ; Bales et al, 2004 ; Lim and Young, 2004 ; Lim et al, 2004 ; Olazábal and Young, 2006 ; Debiec, 2007 ; Donaldson et al, 2010 ; Smith et al, 2010 ; Keebaugh and Young, 2011 ; Cavanaugh et al, 2014 , 2015 , 2018a , 2018b ; Finkenwirth et al, 2016 ; Lieberwirth and Wang, 2016 ; Baxter et al, 2020 ; Razo et al, 2022 ). This is why the determination of OT receptor (OTR) and AVP receptor (AVPr) expression patterns in specific brain regions, and the comparison of such circuits between related monogamous and non-monogamous species, have been the standard procedure to elucidate brain regions involved in the modulation of socio-sexual monogamous behavior ( Shapiro and Insel, 1992 ; Insel et al, 1994 ; Wang et al, 1997b ; Hammock and Young, 2004 ; Smeltzer et al, 2006 ; Freeman et al, 2014 ; Freeman and Young, 2016 ; Smith et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many classical experiments on prairie voles and NWP consisted of pharmacological manipulation of central OTR and AVPr activity, effectively impairing or enhancing pair-bonding behavior ( Winslow et al, 1993 ; Williams et al, 1994 ; Insel et al, 1995b , 1998 ; Insel, 1997 ; Cho et al, 1999 ; Donaldson et al, 2010 ; Smith et al, 2010 ; Johnson et al, 2016 ; Simmons et al, 2017 ; Cavanaugh et al, 2018a , b ). However, these reports lacked the technical advantage of knowing the implications of such manipulations over the interaction with other neurotransmitter systems and brain regions comprising the circuitry.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of OT on investigation and aggression are therefore complex and rely on social context 23 and may modulate behavior and emotion by enhancing an individual’s attunement to its social landscape 24 26 . For example, in marmosets, intranasal OT (IN-OT) increased approach towards an unfamiliar conspecific when a mate was also present but decreased approach when the mate was absent 27 . In humans, IN-OT reduced xenophobic aggression when paired with injunctive prosocial norms of peers, but not when administered without them 28 .…”
Section: Introductionmentioning
confidence: 99%